Genetic analysis of NLRP3 in recurrent pericarditis. (14th October 2021) - Peet, C J; Rowczenio, D; Omoyinmi, E; Capon, F; Lachmann, H J
Abstract: Background: The mechanisms underlying recurrent pericarditis are poorly understood, although the efficacy of colchicine and targeted inhibitors of the interleukin-1 pathway implicate auto-inflammation in its pathogenesis. NLRP3 (NACHT, leucine-rich repeat, and pyrin domain containing protein 3) forms part of the NLRP3 inflammasome that mediates post-translational processing of interleukin-1, and colchicine has also been demonstrated to inhibit this pathway. Pathogenic mutations in exon 3 of NLRP3 cause the auto-inflammatory disease cryopyrin associated periodic syndrome, and the management of this disease and other auto-inflammatory diseases has been transformed over the last two decades by the use of targeted anti-interleukin-1 agents. More recently, NLRP3 inflammasome activity has been demonstrated to be upregulated in the pericardia of patients with recurrent pericarditis. Purpose: Given that mutations in exon 3 of NLRP3 are known to cause auto-inflammatory disease and NLRP3 activity is implicated in recurrent pericarditis, we undertook a genetic analysis of exon 3 of NLRP3 in 99 patients with recurrent pericarditis to determine whether pathogenic mutations in this gene are associated with the disease. Methods: Exon 3 of NLRP3 was analysed either by Sanger (n=30) or amplicon-based next generation (n=69) sequencing. Variants identified by next generation sequencing were validated by Sanger sequencing. Minor allele frequencies were compared to those in the healthy reference population in the Genome Aggregation database (gnomAD) using Fisher's exact test. p values <0.05 were considered statistically significant. Results: No known pathogenic mutations in exon 3 of NLRP3 were identified in 99 patients with recurrent pericarditis. Three patients harboured variants of unknown significance (V198M, T543M, Q703K) in NLRP3. A burden association test comparing the combined frequency of all variants in exon 3 of NLRP3 in this cohort against that observed in healthy controls in gnomAD found no significant difference in allele frequency. Conclusions: This is the first reported genetic analysis of NLRP3 in a cohort of patients with recurrent pericarditis and found no evidence to implicate mutations in this gene in the disease. Whilst access to effective therapies for pericarditis is widening, decisions on treatment duration and identification of patients at risk of recurrent or treatment refractory disease remain significant clinical challenges. Further work exploring the mechanisms by which NLRP3 activity is upregulated in recurrent pericarditis is therefore indicated to identify biomarkers of disease activity and to stratify patients at risk of recurrence. Given the recent successes of agents targeting this pathway in coronary artery disease in clinical trials, such studies may also provide important insights that are of wider interest to the field of cardiovascular medicine. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation Clinical Research Training Fellowship